Isolation, purification and partial characterization of prolamine from the tuberous roots of cassava (Manihot esculenta Crantz) - Grande, Teresa Connie O.
Prolamine, one of the major storage protens of tuberous roots of cassava, Lakan-1 variety, was isolated, purified and partially characterized using biotechmological techniques. Crude prolamine extract (CPE), isolated using the method of Hsu, et al. (1924), contained 0.0652 ug protein/mg sample. Gel filtration chromatography with sephadex G-100 fractionated the crude prolamine according to molecular size. Fractions on the are of major peak were pooled : CSV PF01 cosnisted of the fractions with highest absorbance (peaks) in each of the major peaks per run, while CSV PF02 was the poled fractions other than the highest absorbance (below the peak). The protein content of each pooled fractions were determined to be 0.4215 and 0.3761 ug protein/mg for CSV PF01 and CSV PF02, respectively. SDS-PAGE of the CPE gave a thick band at around 65-70 kDa while CSV PF01 and CSV PF02 fractions gave similar band patterns of two bands one at around 60-65 kDa and the other at 67-70 kDa. CSV PF01 and CSV PF02 fractions contain high amounts of glutamic acid (12.92% - 16.83%), glycine (8.84% - 12.88%), serine (8.34% - 13.68%) and tyrosine (6.38% - 11.47%). Methionine (0.66% - 11.47%) is limiting in both fractions. The proportion of the essential (E) to total (T) amino acids was found to be 49.24% for CSV PF01 and 37.58% for CSV PF02, values which are higher than the recommended ideal protein (36%) by FAO/WHO (1973). Hydrolysis of CPE with multienzyme system is low, indicating poor protein digestibility (67.6%) compared with the standard, casein (73.8% using the pH drop method.